Socio-economic status of Dangi cattle rearers in Ahmednagar district of Maharashtra - VK Kauthale; GJ Bidgar; MAI Sayed; JR Khadse (Journal of Livestock Biodiversity, 2025)
The present investigation was carried out to study the socio-economic status of Dangi cattle owners in Akole block of Ahmednagar district of Maharashtra. A sample of 335 Dangi cattle owners were randomly selected from 7 villages during 2015-16. Primary data was collected through structured questionnaire on family type, land holding, herd size and animal management practices. The results revealed that majority of Dangi farmers (70.75 percent) lived in nuclear family having medium family size (51.94 percent). Majority of the farmers reared Dangi animals for agricultural operations (81.79 percent) with small herd size (57.62 percent). Natural breeding practice (61.79 percent) was preferred to Artificial Insemination. Mostly the animals were allowed for free grazing (85.98 percent). Most of the farmers followed clean milking practices like cleaning udder (96.42 percent) and milking utensils (97.91 percent) etc and also follow vaccination of animals (75.22 percent). The animal housing was in kachha roof (55.82 percent) and kachha loor (87.16 percent) with closed byre (58.81 percent) to protect animals from adverse conditions.